2014
DOI: 10.1021/nl5016975
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles Heat through Light Localization

Abstract: Aqueous solutions containing light-absorbing nanoparticles have recently been shown to produce steam at high efficiencies upon solar illumination, even when the temperature of the bulk fluid volume remains far below its boiling point. Here we show that this phenomenon is due to a collective effect mediated by multiple light scattering from the dispersed nanoparticles. Randomly positioned nanoparticles that both scatter and absorb light are able to concentrate light energy into mesoscale volumes near the illumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
358
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 410 publications
(383 citation statements)
references
References 34 publications
12
358
0
1
Order By: Relevance
“…However, there is no evidence to support the claim that steam production was caused by nanobubbles, i.e., bubbles were formed on top of heated nanoparticles. It should be noted that the solar intensity employed here was 220 Suns, as a few previous work [17,[37][38][39][40][41] has suggested that nanobubbles were unlikely to be generated under relatively low heat fluxes. For example, both Kotaidis et al [42] and Keblinski et al [43] pointed out that a laser power density equivalent to more than Suns was required to form nanobubbles.…”
Section: Steam Generation Mechanismsmentioning
confidence: 99%
“…However, there is no evidence to support the claim that steam production was caused by nanobubbles, i.e., bubbles were formed on top of heated nanoparticles. It should be noted that the solar intensity employed here was 220 Suns, as a few previous work [17,[37][38][39][40][41] has suggested that nanobubbles were unlikely to be generated under relatively low heat fluxes. For example, both Kotaidis et al [42] and Keblinski et al [43] pointed out that a laser power density equivalent to more than Suns was required to form nanobubbles.…”
Section: Steam Generation Mechanismsmentioning
confidence: 99%
“…In a separated theoretical study, of the nanobubble development kinetics around plasmonic gold nanoparticle by Julien et al [51] showed that to generate a nanobubble, a flux intensity of around 1×10 10 W/m 2 was required to 5 generate a nanobubble on a plasmonic gold nanoparticle. However quite differently, Hogan et al [52] reported that ~ 1 MW/m 2 solar reflux was sufficient for efficient steam production due to a collective effect of nanoparticles that both scatter and absorb light, hence localizing light energy into mesoscale volumes.…”
Section: Introductionmentioning
confidence: 98%
“…1B). This process is based on the highly efficient, highly localized photothermal heating (27)(28)(29)(30) induced by solar illumination of broadband light-absorbing NPs, here embedded within the surface layer of the distillation membrane. The localized heating induces vaporization of the feed water, which subsequently condenses on the distillate side of the membrane.…”
mentioning
confidence: 99%
“…The absorption efficiency and spatial distribution of absorbed energy together determine the heat source density, which dictates the solar photothermal temperature increase and thus the water vapor flux through the membrane. Because the CB-laden membrane is a medium that is both strongly optically scattering and absorbing, theoretical calculations using a Monte Carlo photon transport method were necessary to accurately describe the membrane's utility as a photodriven heat source (27). The calculated distribution of absorbed photons ( Fig.…”
mentioning
confidence: 99%